Foot-and-mouth disease virus VP1 promotes viral replication by regulating the expression of chemokines and GBP1 - Yang, Li; Chen, Hong; Liu, Liqing; Song, Jingjing; Feng, Tian; Li, Yihan; Shen, Chao; Kong, Lingbao; Xin, Xiu (Frontiers in Veterinary Science, 2022)
Foot-and-mouth disease virus (FMDV) is an acute, highly contagious, and economically destructive pathogen of vesicular disease that affects domestic and wild cloven-hoofed animals. The FMDV VP1 protein is an important part of the nucleocapsid and plays a significant role during FMDV infection. However, the signal pathways mediated by VP1 in the life cycle of FMDV and the related mechanisms are not yet fully understood. Here, we performed RNA-seq to compare gene expression profiles between pCAGGS-HA-VP1 transfected PK-15 cells and pCAGGS-HA (empty vector) transfected PK-15 cells. The results showed 5571 genes with significantly different expression levels, of which 2981 were up-regulated and 2590 were down-regulated. GO enrichment analysis showed that 51 GO terms were significantly enriched in cell components including protein complex, membrane and organelle part. KEGG enrichment analysis showed 11 KEGG pathways were significantly enriched which were mainly related to the immune system, infectious viral disease, and signal transduction. Among the up-regulated genes, the chemokines such as CCL5, CXCL8 and CXCL10 in turn promoted FMDV replication. In contrast, GBP1, an interferon-stimulated gene that was suppressed by VP1 and FMDV, could effectively inhibit FMDV replication. Our research provides a comprehensive overview of the response of host cells to VP1 protein and a basis for further research to understand the roles of VP1 in FMDV infection including the genes involved in FMDV replication.